Paradigm shift in traditional Mongolian medicine in the 18th century - Damiran, Enkhamgalan; Khailan, Ulaan-Od; Dashjamts, Shagdarsuren; Battogtokh, Gerelmaa; Sharavyn, Bold (Proceedings of the Mongolian Academy of Sciences, 2023)
As Thomas Kuhn stated in his book "The Structure of Scientific Revolutions", revolution is an example of advanced science made by a successful paradigm shift from one to another. At that time, Kuhn's idea was a revolution in itself, becoming the primary method for scientific change. It became a basis for science paradigm policy shift and since, has been a model for gradual reform. Identifying and incorporating this model into the countries' scientific policy and reform is extremely important. The applicability of the used model can be judged by the outcomes resulting in the paradigm shift. By the way, not every scientific progress results in revolution. However, we would like to note that a laggard period with weak mental development is ended by an intellectual outburst. In other words, although in the 17th century, Mongols accepted Tibetan medicine within the framework of the "Four Medical Tantras" with recognition and common scientific mind, later in the 18th century, they thought beyond the box of the "Four Medical Tantras" and created the opportunity to develop a new paradigm. This shift made a valuable contribution to the establishment of, in a broader sense, Mongolian medicine and, in a narrow sense, traditional Mongolian medicine.